G293(P) Defining mild traumatic brain injury: How classification differs across studies when applied to a large prospective data set. a predict prospective cohort study. (24th May 2017) - Crowe, L; Lyttle, MD; Hearps, S; Anderson, V; Borland, M; Phillips, N; Kochar, A; Dalton, S; Cheek, JA; Gilhotra, Y; Furyk, J; Neutze, J; et al.
Abstract : Aims: Mild traumatic brain injury (TBI) in children is a major public health issue, yet there is wide variation in the way 'mild' TBI is defined in the literature and in guidelines. To date no study has prospectively detailed the proportion of children presenting with mild TBI to Emergency Departments (EDs) according to these various definitions. The objective of this study was to apply published definitions of mild TBI to a large prospectively collected data set of childhood head injuries (HIs), and to determine the proportions of mild TBI when the various definitions are applied. Methods: Prospective observational study of children with HIs of any severity presenting to 10 Australian/New Zealand centres. We applied 18 different definitions of mild TBI, identified through a systematic review of the literature, to children aged 3 to 16 years. We assessed the number and percentage of cases the definitions applied to when the specific inclusion and exclusion criteria were used. Results: Of 20 137 children with HI of any severity, 11 907 were aged 3 to 16 years. Mean age was 8.2 years, 32% were female. 61.9% were fall related. Cranial CT rate was 12.7% and neurosurgery rate was 0.5%. Adjustments were made to some definitions to enable application to the data set: none in 7, minor in 9, substantial in 2. Percentages of the cohort covered by the definitions of 'mild' TBI ranged from 2.4% (284) to 98.7% (11, 756) of the cohort. The median percentage of the cohort which was classed as 'mild' TBI using the 18 definitions investigated was 21.7% (2, 589). Conclusions: When applying different definitions of mild TBI to a single data set including all severities, a wide range of cases are included depending on the definition used. Clinicians and researchers need to be aware of this important variability when attempting to apply the published literature to children presenting to EDs with TBI.